Multilevel Current-Source Inverter With FPGA Control - Aguirre, Miguel Pablo (2013)
In this paper, a multilevel current-source inverter (MCSI) topology is analyzed. The issue of constructing a novel modular single-rating inductor MCSI is explored, taking advantage of the features of field-programmable gate arrays (FPGA) for control and gate signal generation. The proposed topology is built with identical modules where all inductors carry the same amount of current, simplifying the construction and operation of industrial applications with higher efficiency. A new state-machine approach, which is easy to implement in an FPGA, and a proper implementation of the phase-shifted carrier sinusoidal pulse width modulation (PSC-SPWM) allow both current balance in all modules and effective switching-frequency minimization. The performance of the MSCI proposed is simulated with Matlab and is verified by constructing a prototype.